The Shifting of the Demonstrative Determiner in French and Dutch in Parallel Corpora: From Translation Mechanisms to Structural Differences - Vanderbauwhede, Gudrun; Desmet, Piet; Lauwers, Peter (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2011)
This paper focuses on translational shifts with respect to the demonstrative determiner in French and Dutch in parallel corpora. The paper aims to identify the types of translation shifts that occur systematically, and to explore the underlying mechanisms and semantic effects of this process. For this purpose, a well-balanced sub-corpus of the Dutch Parallel Corpus is used, making it possible to analyze both directions (French – Dutch and Dutch – French). In this corpus, 50% of the demonstrative determiners are translated by a demonstrative in the target text (in both directions). In 20% of the cases, the demonstrative is translated by a definite article, or vice versa, while 30% are translated by another grammatical element (e.g., indefinite determiner, adverb, personal pronoun) or vice versa. The parallel corpus study reveals that translational shifts with respect to French and Dutch demonstratives can be attributed to three different mechanisms: (1) translator preference related to translation universals at the level of the noun phrase (omissions, additions and reformulations of the noun phrase), (2) specific manifestations of translation universals within the noun phrase (syntagmatic and paradigmatic explicitation and implicitation involving demonstrative shifting) and (3) structural divergences between the French and Dutch demonstrative determiner systems (fixed expressions and semantic differences). This analysis demonstrates the usefulness of a detailed parallel corpus study, which clearly distinguishes between changes occurring at different levels, in accounting for divergent translations of the demonstrative determiner in different languages. To this end, several types of explanation drawn from various fields (such as translation studies and contrastive linguistics), must be considered.